Math, asked by Anonymous, 8 months ago

Find the integration of
\displaystyle \sf \: \int \frac{ \sin^{2}x - \cos ^{2} x}{ \sin \: x. \cos \: x}

Lo karo answer mera level ka nhi hai. Google se mila​

Answers

Answered by Anonymous
2

\LARGE{\bf{\underline{\underline\color{blue}{GIVEN:-}}}}

\sf \bullet \ \ \dfrac{(1+sinA-cosA)^2}{(1+sinA+cosA)^2} = \dfrac{1-cos}{1+cos}

\LARGE{\bf{\underline{\underline\color{blue}{SOLUTION:-}}}}

LHS:

\sf \to \dfrac{(1+sinA-cosA)^2}{(1+sinA+cosA)^2}→

Expand the fractions using (a+b+c)²=a²+b²+c²+2ab+2bc+2ca.

\sf \to \dfrac{(cos^2-2sincos+sin^2-2cos+2sin+1)}{(cos^2+2sincos+sin^2+2cos+2sin+1)}→

Rearrange the terms.

\sf \to \dfrac{(cos^2+sin^2-2sincos-2cos+2sin+1)}{(cos^2+sin^2+2sincos+2cos+2sin+1)}→

We know that cos²A+sin²A=1.

\sf \to \dfrac{1-2sincos-2cos}{2sin+1}→

Now here, take -2cos common from the numerator and +2cos common from the denominator.

\sf \to \dfrac{1-2cos(sin+2)}{2sin+1}→

Now, rearrange the terms, add 1 and 1 and take 2 common.

 \to\sf\dfrac{1+1+2sin-2cos}{sin+1}→

\to\sf\dfrac{2+2sin-2cos}{sin+1}→

Take 2 common.

\to \sf \dfrac{ 2(1+sin) -2cos(sin+1) }{ 2(1+sin) + 2cos(sin +1 ) }→

\to \sf{\red{\dfrac{1-cosA}{1+cosA} }}→ </p><p>

LHS=RHS.

HENCE PROVED!

FUNDAMENTAL TRIGONOMETRIC RATIOS:

\begin{gathered}\begin{gathered}\boxed{\substack{\displaystyle \sf sin^2 \theta+cos^2 \theta = 1 \\\\ \displaystyle \sf 1+cot^2 \theta=cosec^2 \theta \\\\ \displaystyle \sf 1+tan^2 \theta=sec^2 \theta}}\end{gathered}\end{gathered}

T-RATIOS:

\begin{gathered}\begin{gathered}\boxed{\boxed{\begin{array}{ |c |c|c|c|c|c|} \bf\angle A &amp; \bf{0}^{ \circ} &amp; \bf{30}^{ \circ} &amp; \bf{45}^{ \circ} &amp; \bf{60}^{ \circ} &amp; \bf{90}^{ \circ} \\ \\ \rm sin A &amp; 0 &amp; \dfrac{1}{2}&amp; \dfrac{1}{ \sqrt{2} } &amp; \dfrac{ \sqrt{3} }{2} &amp;1 \\ \\ \rm cos \: A &amp; 1 &amp; \dfrac{ \sqrt{3} }{2}&amp; \dfrac{1}{ \sqrt{2} } &amp; \dfrac{1}{2} &amp;0 \\ \\ \rm tan A &amp; 0 &amp; \dfrac{1}{ \sqrt{3} }&amp; 1 &amp; \sqrt{3} &amp; \rm Not \: De fined \\ \\ \rm cosec A &amp; \rm Not \: De fined &amp; 2&amp; \sqrt{2} &amp; \dfrac{2}{ \sqrt{3} } &amp;1 \\ \\ \rm sec A &amp; 1 &amp; \dfrac{2}{ \sqrt{3} }&amp; \sqrt{2} &amp; 2 &amp; \rm Not \: De fined \\ \\ \rm cot A &amp; \rm Not \: De fined &amp; \sqrt{3} &amp; 1 &amp; \dfrac{1}{ \sqrt{3} } &amp; 0 \end{array}}}\end{gathered}\end{gathered}

Answered by Anonymous
3

Answer:

★ Formula Applied :

\begin{gathered}\sf \bullet\ \; cos^2x-sin^2x=cos2x\\\\\to\ \sf \pink{sin^2x-cos^2x=-cos2x}\end{gathered}

\begin{gathered}\bullet\ \; \sf sin2x=2.sinx.cosx\\\\\to \sf \blue{sinx.cosx=\dfrac{sin2x}{2}}\end{gathered}

\displaystyle \bullet\ \; \sf \int \dfrac{dx}{x}

\bullet\ \; \sf \ln (ab)=\ln a+\ln

★ Explanation :

\begin{gathered}\displaystyle \sf \int \dfrac{sin^2x-cos^2x}{sinx.cosx}dx\\\\\to \sf \int \dfrac{-cos2x}{\frac{sin2x}{2}}dx\\\\\to \sf \int \dfrac{-2cos2x}{sin2x}dx\end{gathered}

Lets use substitution method ,

Let , u = sin2x

⇒ du = 2.cos2x.dx

\begin{gathered}\to \displaystyle \sf \int \dfrac{-du}{u}\\\\\to \sf -\int \dfrac{du}{u}\\\\\to \sf -ln|u|\\\\\end{gathered}

\to \sf \red{-ln|sin2x|+c}

\to \sf - \ln |2sinx.cosx|+c

\to \sf - \ln |sinx.cosx|+(\ln 2+c)

\leadsto - \sf \red{\ln |sinx.cosx|+c}\ \; \bigstar

★ Alternate Method :

\displaystyle \sf \int \dfrac{sin^2x-cos^2x}{sinx.cosx}

\displaystyle \to \sf \int \left( \dfrac{sin^2x}{sinx.cosx}-\dfrac{cos^2x}{sinx.cosx}\right)dx

\begin{gathered}\displaystyle \to \sf \int \left( \dfrac{sinx}{cosx} -\dfrac{cosx}{sinx} \right)dx\\\\\to\ \sf \int (tanx-cotx)dx\\\\\to \sf \int tanx.dx-\int cotx.dx\\\\\to \sf ln|secx|-ln|sinx|+c\end{gathered}

\to \sf ln\left| \dfrac{secx}{sinx}\right|+c

\begin{gathered}\to \sf ln\left| \dfrac{1}{sinx.cosx} \right|+c\\\\\end{gathered}]

\leadsto \sf \pink{-ln|sinx.cosx|+c}\ \; \bigstar

Similar questions